PENGARUH KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN BIREUEN - Ferri; Ida; M. (JURNAL KEBANGSAAN, 2023)
This research aims to analyze the influence of Leadership and Organizational Climate on Employee Performance, taking the number of respondents as a research sample of 49 respondents who are Civil Servants (PNS) who work at Badan Perencanaan Pembangunan Daerah (BAPPEDA) of Bireuen District to be distributed questionnaires. The analytical method used in this study is Multiple Linear Regression Analysis where this analysis can be used to see the relationship and influence between the variables studied. Based on the analysis and calculation of the research results obtained a strong and positive relationship between Leadership and Organizational Climate on Employee Performance, with a correlation coefficient of 0,719 and a linear equation Y = 2,141 + 0,272X1 + 0,276X2. The results showed that there was a partial and simultaneous influence between Leadership and Organizational Climate on Employee Performance. The results of the research also show that 51.7% of the Performance of Civil Servants (PNS) at Badan Perencanaan Pembangunan Daerah (BAPPEDA) of Bireuen District can be explained by the variables of Leadership and Organizational Climate. The remaining 48.3% is influenced by other variables outside of this research.